STREAM (Spatial tools for river basins and environment and analysis of management options): ‘set up and requirements’ - Aerts, J.C.J.H.; Kriek, M.; Schepel, M. (Physics and chemistry of the earth. Part B, Hydrology, oceans and atmosphere, 1999)
The STREAM instrument (Spatial Tools for River basins and Environment and Analysis of Management options) is an instrument for river basin studies with emphasis on management aspects. STREAM uses a spatial distributed water balance model for simulating the water balance in large river basins. This model enables the analysis of the impacts of climate change and land use changes on the fresh water hydrology of a river basin. The instrument uses remotely sensed data for determining land use. STREAM has been applied for several river basins around the world as the Rhine-, Ganges/Brahmaputra, Amudarya and the Yangtze basin. An important issue related to river basin management studies for these regions is how to maintain the natural resources in the basin in order to satisfy the needs for food and water for the population. This paper gives an overview of the concepts and tools used by STREAM with some examples of input and output data.